2014
DOI: 10.5812/cardiovascmed.20159
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing prolonged icu stay after open heart surgery

Abstract: Background:There are different risk factors that affect the intensive care unit (ICU) stay after cardiac surgery.Objectives:The aim of this study was to evaluate possible risk factors influencing prolonged ICU stay in a large referral hospital.Patients and Methods:We conducted a case-control study to determinate causes of prolonged ICU stay in 280 adult patients undergoing cardiac surgery in a tertiary care center for cardiovascular patients, Tehran, Iran. These patients were divided into two groups according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 16 publications
(16 reference statements)
2
24
0
1
Order By: Relevance
“…A study by Azarfarin (2014), revealed that patients with heart failure functional classes III and IV increased ICU length of stay, postoperative stroke incidence and postoperative kidney failure. 12 In this study the status of patients with clinical heart failure functional class IV was not found. This is likely because patients with functional IV grade heart failure rarely achieve optimal conditions for surgery.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…A study by Azarfarin (2014), revealed that patients with heart failure functional classes III and IV increased ICU length of stay, postoperative stroke incidence and postoperative kidney failure. 12 In this study the status of patients with clinical heart failure functional class IV was not found. This is likely because patients with functional IV grade heart failure rarely achieve optimal conditions for surgery.…”
Section: Resultsmentioning
confidence: 56%
“…This finding resembles the results of Azarfarin's (2014) study of factors related to the increased of length of stay after open heart surgery which stated that age >50 years, duration of surgery and CPB duration had a significant effect on ICU length of stay. 12 Another study that discussed the duration of CPB was carried out by Salis et al (2008) which states that CPB duration is an independent predictor of postoperative cardiac morbidity and mortality. The type of morbidity studied by Salis et al are postoperative blood loss, length of ICU treatment, total length of hospital stays, multiple RBC transfusions, surgery due to bleeding, respiratory, neurological, infection, and kidney complications.…”
Section: Vol 43 No 1 2020mentioning
confidence: 99%
“…Other research showed that in elderly age group, low LVEF, the duration of CPB, and repetitive surgeries helped play a role in long hospitalization in intensive care unit. Moreover, it was found in patients with LVEF less than 40% of the time required is much longer to achieve stable hemodynamics and weaned from mechanic ventilation so as to extend the period of treatment in the intensive care room [6] [13].…”
Section: Discussionmentioning
confidence: 99%
“…Estudos sugerem que a ventilação mecânica invasiva (VMI) prolongada resulta em maiores índices de mortalidade, 6 além da diminuição da capacidade pulmonar e aumento da chance de complicações pulmonares 7,4 . Em contrapartida, um tempo menor de VMI reduz o tempo de permanência hospitalar por acelerar a fase de recuperação pós-operatória e a mobilidade do paciente 8 . Por isso, torna-se importante identificar fatores que possam contribuir para melhorar esse desfecho.…”
Section: Introductionunclassified